ANALISIS KETERLAKSANAAN PROSES PEMBELAJARAN FISIKA DI MAN KOTA BLITAR MELALUI PENGAMATAN VIDEO PEMBELAJARAN MENGGUNAKAN TBLA PADA MATERI SUHU DAN KALOR - Asmara, Popi; Susanti, Nova; Alrizal, Alrizal; Mufidah, Imroatul (JURNAL PEMBELAJARAN FISIKA, 2024)
This research by observing Transcript Based Lesson Analysis based learning videos can determine the effectiveness of students' learning process on temperature and heat material. To analyze the implementation or not of physics learning through video observations using Transcript Based Lesson Analysis with learning tools, namely using the Problem Based Learning model. This research was conducted at MAN Blitar City. This research uses a qualitative research approach to describe or describe the analysis of a learning process using TBLA. This type of research is a case study. The data in this research is in the form of qualitative research data. The procedure uses data reduction, data presentation and conclusions. This research uses a saturated sampling technique which is included in non-probability sampling. Based on the learning tools, these learning activities are categorized as carried out according to the learning tools that use the PBL model, where the teacher guides students to discuss, open learning, motivate, provide reflection, provide information on learning for the following week and so on